2016
DOI: 10.1590/1678-457x.0017
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of supercritical fluid CO2 extracts from freeze-dried powder of Tenebrio molitor larvae (yellow mealworm)

Abstract: In order to take full advantage of Tenebrio molitor larvae (yellow mealworm) resources, the supercritical CD 2 fluid freeze-dried powder of T. molitor larvae (fdTML) extraction on the immune systems of mice was carried out. The results about the effects of supercritical CD 2 fluid fdTML extraction on carbon expurgation and phagocytosis of peritoneal macrophages experiments of mice indicated that the fdTML extraction enhanced observably carbon expurgatory index, phagocytic rate and phagocytic index. The fdTML e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In vivo studies on mice model revealed that freeze dried Tenebrio molitor larvae enhance the phagocytic activity of macrophages in mice. It produces immunomodulatory effects by intensifying the non-specific, cellular and antibody mediated immune responses (Tang and Dai, 2016).…”
Section: Immunomodulatory Effects Of Edible Insect Extracts and Activ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies on mice model revealed that freeze dried Tenebrio molitor larvae enhance the phagocytic activity of macrophages in mice. It produces immunomodulatory effects by intensifying the non-specific, cellular and antibody mediated immune responses (Tang and Dai, 2016).…”
Section: Immunomodulatory Effects Of Edible Insect Extracts and Activ...mentioning
confidence: 99%
“…Other insect peptides show their immunomodulatory activity by enhancing the maturation of DC and NK cells. This in turn activates T CD8 + cell and destroy cancer cells (Tang and Dai, 2016). Insect derived lectins show anti-cancer immunomodulatory activity through M1 macrophage mediated phagocytosis (Cao et al, 2012).…”
Section: Immunomodulatory Effects Of Edible Insect Extracts and Activ...mentioning
confidence: 99%
“…Female mice were used to study the immunomodulatory potential of Cn on CP induced mice model since female mice exhibit stronger innate and adaptive immune responses and stronger antibody responses compared to the male counterparts [30]. Moreover, many researchers have also used female mice to study immunomodulatory responses in edible insects like Tenebrio molitor larvae [23], Oxya chinensis sinuosa (grasshopper species) [24], Polyrhachis vicina (Chinese Black ant) [22].…”
Section: Model Animalmentioning
confidence: 99%
“…The optical density (OD) values were measured at the wavelength of 570 nm with a Universal Microplate Spectrophotometer. The difference in OD values between the samples incubated with and without Con A represented the proliferation ability of splenic lymphocytes as described by Tang et al [37].…”
Section: Lymphocyte-proliferation Testmentioning
confidence: 99%
See 1 more Smart Citation